Internalisasi Nilai-Nilai Agama Islam melalui Pembelajaran PAI di SDN 5 Pasui - Izharuddin H (Universitas Muhammadiyah Enrekang, 2022)
Education in Indonesia in the last decade has had many problems, one of which is the decay of the morals of the younger generation and this is an important discussion that deserves our attention. The essence of the purpose of Islamic Religious Education in general is to form students to become human beings who fear Allah and have noble character. Seeing this problem, it is necessary to have a breakthrough, one of which is through the internalization of Islamic religious values ​​through learning programs in class, especially PAI learning and activities outside school hours. This study aims to: (1) to find out the implementation of the internalization of Islamic religious values ​​through learning PAI, (2) to find out the implementation of the internalization of Islamic religious values ​​to shape the morale of children at SDN 5 Pasui. This study uses a descriptive qualitative approach. Collecting data through observation, interviews, and documentation. As well as data analysis using the triangulation method. The results showed that: (1) the internalization of Islamic religious values ​​at SDN 5 Pasui through learning PAI was carried out in several stages: 1) Value transformation stage 2) Value transaction stage 3) Transinternalization stage. (2) the process of internalizing Islamic religious values ​​to shape the morale of children at SDN 5 Pasui is carried out through activities outside of school hours as follows: Faith values ​​through prayer programs before and after learning, moral values ​​through 3S activities (Smiles, Greetings and Sapa) and Sharia Values ​​with congregational duha prayers, congregational dhuhur prayers and the qira'ati program.